Pediatric otitis media post cochlear implant retrospective cohort study - Deghadey, Abdallah Atwa El; Elzayat, Saad Eldesoky; Mekhimar, Sayed Mahmoud; Kadah, Sayed Mohamed Saied; Mostafa, Soad Yehia (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: A cochlear implant (CI) is a greatly effective therapy for severe to profound deafness. This study aims to examine the prevalence of otitis media (OM) in children after CI and its impact on the device’s integrity with reporting the various management policies and results. Methods: This retrospective cohort study included 307 children, aged one to five years, who had CIs performed by the surgical team between January 2016 and December 2019. A detailed pre, intra, and postoperative data collected from these patients’ medical records was reviewed retrospectively by the same surgical team. Results: There is a statistically significant difference in the distribution of OM in the operated ears; the p value was <0.001. There is a statistically significant association between post-implant OM and getting implantation, as the p value was <0.001. Multivariate analysis showed significant associations between post-implant OM and a history of receiving vaccination (no), a perioperative history of otitis media with effusion (yes), and a history of recurrent tonsillitis and enlarged adenoids (yes) (p value< 0.05). Conclusions: In children, the prevalence of developing post-implant OM in the implanted ears does not rise, but rather falls, contradicting the theory that foreign bodies may aggravate the infection. Our findings supported the safety of CI in children with a history of post-implant OM, as all cases of post-implant OM were managed medically, with no additional surgical intervention required. Furthermore, no case had any significant complications, such as meningitis, or had a negative impact on the device’s integrity.